O gênero aforismo no ensino fundamental: uma proposta de leitura e escrita - Venâncio, Annecy Bezerra (2020)
In this dissertation, we focus on an intervention project that aimed to establish Aphorism as an important textual resource for the critical and social development of 9th grade students. Thinking about the teaching of the Portuguese language presupposes, among several factors, a careful reflection regarding its value for the formation of the reader. Thus, we understand that the use of aphorisms, in the classroom, favors the promotion of literary literacy, mainly because it constitutes, at the same time, a brief and dense interpretation genre, allowing to walk on several subjects. The study, of qualitative nature and of a descriptive-interventionist character, took place with 9th grade students from a state school in the city of Goiana-PE. This study consisted of the researcher's direct contact with students participating in the research. The approached method gained more precise contours with the Basic Sequence, proposed by Rildo Cosson. In order to theoretically base our research, we will be guided by the official documents that govern Education in Brazil, such as: the National Common Curricular Base (BNCC) and the National Curriculum Parameters (PCN) of Elementary Education. In addition to these, we used the Pedagogical Political Project (PPP) of the target school of the project. We also seek support, in Cosson's theoretical perspectives (2016), with regard to Literary Literacy and Basic Sequence; de Pinheiro (2007), about Poetry in the Classroom; Bakhtin (1992) with his studies on textual genre; Colomer (2003), Koch and Elias (2018), in their studies on Reading and Writing; Geary (2007) and Neto (2017), in the elaborations on Aphorism; and Thiollent (2011), when dedicated to the methodological directions of Action Research. We emphasize that this study was of great importance for the recognition of Aphorism within the literature, as well as its positioning in the social formation of the elementary school student.